Experience of registered nurses in assessing postoperative pain in hip fracture patients with dementia - Ferid Krupić; Sahmir Sadić; Nail Seffo; Mirza Bišćevic; Mirsad Fazlić; Svemir Čustović; Kristian Samuelsson (Medicinski glasnik, 2017)
Aim: To explore the experience of registered nurses in assessing pain in hip fracture in patients with dementia in the postoperative setting. Methods: The study questionnaire contained 23 items mainly addressing demographic and social data, information about communication and pain assessment, attention and awareness of the health-care professionals on the ward and suggestions for improving nursing. Results: The nurses claimed that they began their assessment of pain in patients with dementia first by observing the patient and making a visual assessment of pain, after which they began to communicate with these patients; majority of dementia patients with hip fractures displayed more facial expressions of pain than patients without dementia. All the nurses agreed that the more severe the patient's dementia was, the less clear the facial expressions and that this in turn made it difficult for the nurses to take care of such patients. Body language was the most common way the patients with dementia and hip fractures expressed their pain. Assessing the pain of a dementia patient with hip fracture and interpreting a non-verbally communicative patient was experienced as very difficult by all the nurses. Conclusion: The nurses found that the fact that they had not attended any courses on dementia and pain assessment in those patients made their work more difficult; they need to know more and to have more information about those patients and their needs for a more comprehensive exchange of information between the hospital wards and the patients' care homes.
Keywords: dementia disease; hip fracture; pain assessment; registered nurses; qualitative research